A multi-dimensional evaluation of craving and impulsivity among people admitted for alcohol-related problems in emergency department. (February 2019) - Flaudias, Valentin; Teisseidre, Frederique; De Chazeron, Ingrid; Chalmeton, Maryline; Bertin, Celian; Izaute, Marie; Chakroun-Baggioni, Nadia; Pereira, Bruno; Brousse, Georges; Maurage, Pierre
Highlights: It's explored people admitted for alcohol-related problems in emergency department. Craving is more linked with alcohol-related severity than impulsivity. Particularly for the compulsive dimension of craving. Interest of using simple craving assessment (i.e. VAS) in clinical settings. Abstract: Craving and impulsivity are key psychological dimensions involved in the development and maintenance of severe alcohol-use disorders. This study proposes an integrative evaluation of craving (Visual Analogue Scale, VAS and Obsessive Compulsive Drinking Scale, OCDS) and impulsivity (UPPS Scale and Barratt Impulsiveness Scale) among patients admitted in emergency department for alcohol misuse. Ninety-eight patients were included. Regression analyses showed that the scores obtained at the compulsive subscale of the OCDS, at the VAS and at the Urgency subscale of impulsivity constitute the main predictors of the severity of alcohol-use disorders (indexed by the AUDIT). These results suggest that specific sub-dimensions of craving and impulsivity may play a critical and joint role in the maintenance of excessive alcohol consumption.